Comprehensive molecular and morphological resolution of blubber stratification in a deep-diving, fasting-adapted seal - J. I. Khudyakov; K. N. Allen; D. E. Crocker; N. S. Trost; A. H. Roberts; L. Pirard; C. Debier; E. R. Piotrowski; J. P. Vázquez-Medina (Frontiers in Physiology, 2022)
Blubber is a modified subcutaneous adipose tissue in marine mammals that provides energy storage, thermoregulation, hydrodynamic locomotion, and buoyancy. Blubber displays vertical stratification by lipid content, fatty acid composition, and vascularization, leading to the assumption that deeper blubber layers are metabolically active, while superficial layers are mainly structural and thermoregulatory. However, few studies have examined functional stratification of marine mammal blubber directly, especially in pinnipeds. We characterized morphological and transcriptional differences across blubber layers in the northern elephant seal, a deep-diving and fasting-adapted phocid. We collected blubber from seals early in their fasting period and divided blubber cores into three similarly sized portions. We hypothesized that the innermost blubber portion would have higher 1) heterogeneity in adipocyte size, 2) microvascular density, and 3) expression of genes associated with metabolism and hormone signaling than outer blubber. We found that adipocyte area and variance increased from outermost (skin-adjacent) to innermost (muscle-adjacent) blubber layers, suggesting that inner blubber has a higher capacity for lipid storage and turnover than outer blubber. Inner blubber had a higher proportion of CD144+ endothelial cells, suggesting higher microvascular density. In contrast, outer blubber had a higher proportion of CD4+ immune cells than inner blubber, suggesting higher capacity for response to tissue injury. Transcriptome analysis identified 61 genes that were differentially expressed between inner and outer blubber layers, many of which have not been studied previously in marine mammals. Based on known functions of these genes in other mammals, we suggest that inner blubber has potentially higher 1) adipogenic capacity, 2) cellular diversity, and 3) metabolic and neuroendocrine signaling activity, while outer blubber may have higher 1) extracellular matrix synthesis activity and 2) responsiveness to pathogens and cell stressors. We further characterized expression of nine genes of interest identified by transcriptomics and two adipokines with higher precision across blubber layers using targeted assays. Our study provides functional insights into stratification of blubber in marine mammals and a molecular key, including CD144, CD4, HMGCS2, GABRG2, HCAR2, and COL1A2, for distinguishing blubber layers for physiological and functional studies in seals.